Auchenorrhyncha types (Hemiptera) deposited in Hayk Mirzayans Insect Museum - Mozaffarian, Fariba (Zootaxa, 2017)
A list of type material of Auchenorrhyncha deposited in Hayk Mirzayans Insect Museum is provided including the latest accepted names, full citation, collecting data and the type status of the specimens. A total of 66 type species and 1 subspecies (15 Holotypes, 2 Allotypes and 63 Paratypes) are listed which consist of 278 specimens (15 Holotypes, 2 Allotypes and 261 Paratypes). Three of the species names were later considered as junior synonyms of previously published species, 7 species are considered in new combinations currently and 2 of them were actually never described.